Profile of ecological practicum, logical thinking, and system thinking pre-service biology teacher - Suhendar; Rini Solihat (Universitas Negeri Jakarta, 2023)
Ecology is a complex system, so it requires thinking skills to understand it. One of the skills that can be trained in ecological practicum lectures is systems thinking skills. Ecology practicum has the potential and strategic role in preparing quality students to face the era of industrialization and globalization. This potential will be realized if practicum activities can equip students with the ability to think logically, think creatively, think critically, and think systems, which ends up being able to solve integrated problems. To design an ecology practicum program that can train systems thinking skills, it is necessary to know the existing forms of ecological practicum implementation, students' systems thinking skills, and their logical thinking skills. This study aims to obtain information on the description of these three things so that it becomes the basis for developing a better practicum program. and adaptive to changes and developments of the times. This research is in the form of field research, namely research whose object is about the symptoms or events that occur in the subject group. 18 third-level students and 39 fourth-level students were selected as research subjects. Limited interviews were conducted with practicum assistants and course lecturers. The instrument used consisted of a logical thinking ability test, systems thinking scale, systems thinking test, and interview guidelines. The results of the study show practicum activities only practice the skills of collecting, processing, and analyzing ecological data. Students' logical thinking ability is in a “good” category, especially at the level of combinatorial reasoning. Students' systems thinking ability is low, especially forest thinking skills.